Numerical solution of fractional order COVID-19 model via the generalized fractional Adams-Bashforth-Moulton approach - Onoja, T.U.; Amos, J.; Atokolo, W.; Abah, E.; Omale, D.; Bolaji, B. (International Journal of Mathematical Analysis and Modelling, 2026)
The objective of the paper is to conduct an inquiry of a few of the epidemiological characteristics of COVID-19 infection by invoking a fractional-order mathematical framework in measuring the impact of vaccination and treatment to the dynamics of the spread of COVID-19. It qualifies the conditions of existence and uniqueness of the solution of the model in the fractional repetition and stabilities the endemic equilibrium by the use of the method of the Lyapunov function. The sequence of numerical simulations that used the fractional Adams-Bashforth Moulton approach elaborates on the role played by the chosen model parameters, and the fractional-orders values improving the control and dynamics of COVID-19. Additional mathematical simulations that utilize surface and contour plots indicate that the prevalence of COVID-19 would be higher in case of higher contact rates and lower efficiency of treatment. The study further establishes that an optimal strategy on vaccination and treatment would end up countering the high rate of COVID-19 among the population.